Six concepts in search of retirement. Issue 1 (2nd January 2017) - Katz, Elihu; Fialkoff, Yonatan
ABSTRACT: We propose, provocatively, some examples of concepts – however foundational – that deserve to be 'retired' because (1) they are poorly named or have multiple names, (2) the hypotheses associated with them are only weakly confirmed by empirical testing, (3) they are so vague or ambitious that they are of little further use, (4) they are poorly conceptualized, (5) they are poorly operationalized, (6) the world (e.g. new media) has made them obsolete. Nevertheless, we agree that they may remain 'good to think with.'